2019
DOI: 10.1177/0963721419838242
|View full text |Cite
|
Sign up to set email alerts
|

Is Nothing Sacred? Religion, Sex, and Reproductive Strategies

Abstract: Religion has often been conceptualized as a collection of beliefs, practices, and proscriptions that lift people’s thoughts and behaviors out of the metaphorical gutter of sex and selfishness toward lives full of meaning, contemplation, and community service. But religious beliefs and behaviors may serve selfish, sexual motivations in ways that are not always obvious or consciously intended. We review two lines of research illustrating nonobvious links between the mundane and the religious. First, contrary to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 24 publications
1
25
1
2
Order By: Relevance
“…In line with these observations, religions' adherents tend to be viewed as trustworthy (Hall, Cohen, Meyer, Varley, & Brewer, 2015;McCullough, Swartwout, Shaver, Carter, & Sosis, 2016;Tan & Vogel, 2008) and this trustworthiness is linked to perceived reproductive strategies (Moon, Krems, & Cohen, 2018;Moon et al, 2019). That is, people tend to trust religious targets more than nonreligious targets because of their supposed adherence to long-term mating strategies, including more restricted sexual orientations and reduced sexual promiscuity, male abandonment, and female cuckoldry.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…In line with these observations, religions' adherents tend to be viewed as trustworthy (Hall, Cohen, Meyer, Varley, & Brewer, 2015;McCullough, Swartwout, Shaver, Carter, & Sosis, 2016;Tan & Vogel, 2008) and this trustworthiness is linked to perceived reproductive strategies (Moon, Krems, & Cohen, 2018;Moon et al, 2019). That is, people tend to trust religious targets more than nonreligious targets because of their supposed adherence to long-term mating strategies, including more restricted sexual orientations and reduced sexual promiscuity, male abandonment, and female cuckoldry.…”
mentioning
confidence: 76%
“…Religion Causes Decreases in Women's Provocativeness of Dress Several individual differences in characteristics such as age (Kenrick & Keefe, 1992) 1992), personality (Pines, 1998), and sociosexual orientation (Provost, Troje, & Quinsey, 2008) influence the mating strategies that men and women pursue. Recently, research has evaluated the utility of religiosity in long-term mating strategies (Moon, Krems, Cohen, & Kendrick, 2019) because religiosity is a known predictor of restricted sexual attitudes, behaviors, and fantasies (Aalsma et al, 2013;Ahrold, Farmer, Trapnell, & Meston, 2011) associated with long-term orientations. That is, Reproductive Religiosity Theory posits that people strategically use their religious beliefs, religious attendance, and religious group affiliations to support a long-term mating strategy, and to buffer against the costs affiliated with this mating strategy (Weeden, Cohen, & Kenrick, 2008;Weeden & Kurzban, 2013).…”
mentioning
confidence: 99%
“…Our results also showed that support for veiling (an indicator of sexual conservative morality) is associated with importance of religion. Similarly, recent evidence has shown that in line with Reproductive Religiosity Model (Weeden et al, 2008; Weeden & Kurzban, 2013) religious belief and norms serve to moralize sexual promiscuity (Jacquet et al, 2020; Moon et al, 2019; Van Slyke & Szocik, 2020). Accordingly, all religious traditions condemn extramarital sexual relations (Burdette et al, 2007) and religiosity regulates female sexuality in favor of males’ paternity (Pazhoohi, Lang, et al, 2017; Strassmann et al, 2012) eliciting higher paternal care and family ties (Anderson et al, 2007; Pashos & McBurney, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Moralizing sexual promiscuity EVS model 2.1. A number of recent studies suggest that religiosity might by primarily associated with a willingness to moralize behaviors deviating from sexual monogamy, but less with freeriding (for a recent review, see Moon et al, 2019). In line with these works, we model moralizing attitudes separately for promiscuous sexual behaviors and free-riding.…”
Section: Religiositymentioning
confidence: 94%
“…The second class of models test Hypothesis 2 according to which higher social mistrust leads individuals to higher religiosity through increased moralization of other people's behaviors. This second class involves models focusing on attitudes aiming to moralize sexual promiscuity to specifically expand on the predictions derived from the "Reproductive religiosity hypothesis" (for a review, see Moon et al, 2019) (models 2.1), and models focusing on attitudes aiming to moralize free-riding (models 2.2).…”
Section: Introductionmentioning
confidence: 99%